Paket Pendidikan Kesehatan "Siaga" terhadap Kesiapan Ibu Pasca Abortus untuk Hamil Kembali - Yessi Andriani; Andrye Fernandes (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of the "Siaga" health education package on the readiness of post-abortion mothers to become pregnant again. This research method is quantitative with a quasi-experimental design with a pretest-posttest approach with a control group. The results showed that most post-abortion mothers, both the intervention group and the control group, had secondary education, namely 65.9%. The majority did not work or were homemakers, as many as 27 people (54%). Most families have sufficient income, more than the UMR Bukittinggi, namely 31 people (62%). Most of them did not have children, namely 15 people (44.1%), and had a history of abortion at most once, namely nine mothers (36%) in the intervention group and as many as 12 people (48%) in the control group. Based on bivariate analysis, the mean difference in readiness in the intervention group was 13.92 (p=0.001; Î± p<0.05), while in the control group, it was only 0.62. In conclusion, the effect of providing health education packages on the readiness of post-abortion mothers to become pregnant again. There was a significant difference between the readiness of post-abortion mothers before and after being given the intervention, with the mean difference in the intervention group being more important than the difference in the control group. Keywords: Abortion, Pregnancy Readiness, Health Education